Easier said than done: Obstacles to the expansion of secondary education in Uruguay - María Ester Mancebo; Julia Pérez Zorrilla (Arizona State University, 2018)
In 2008, the Uruguayan General Education Law was enacted, stipulating the right to education and extending compulsory education from nine to fourteen years. This article analyzes the obstacles to design and implement educational policies to improve secondary education attainment rates during the governments headed by the Frente Amplio party from 2005 on. Using a qualitative approach, we employed a triangulation method that includes document analysis (laws and institutional reports) and 49 semi-structured interviews conducted between 2011 and 2015; the interviews covered government authorities, legislators, bureaucrats, experts and union leaders. We identified three potential causes of this policy gridlock: the institutional fragmentation of the educational system; the ideological disagreement between educational authorities and party members; and the teacher's union veto. The educational policy stalemate in secondary education is explained by these multiple factors and their interaction.